2014
DOI: 10.1111/1750-3841.12645
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gram‐Negative Psychrotrophic Bacteria isolated from Italian Bulk Tank Milk

Abstract: Eighty psychrotrophic bacterial strains, isolated from different northwest Italian bulk tank milks destined for Grana Padano cheese production, were identified by 16S rRNA gene amplification and partial sequence analysis of the rpoB gene. Pseudomonas spp. were the most commonly occurring contaminants, P. fluorescens being the predominant isolated species, along with Enterobacteriaceae, primarily Serratia marcescens. RAPD-PCR was used to study genetic variability and distinguish closely related strains; a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 78 publications
3
59
1
2
Order By: Relevance
“…Serratia spp. were also detected in raw milk samples stored at 4 °C for 24 h (Lafarge and others ), in bulk tank milk (Decimo and others ) and in a milk‐processing plant (Cleto and others ), but these authors did not evaluate the capacity of heat‐resistant proteolytic enzymes production of Serratia isolates. Teh and others (), in addition to isolating S. liquefaciens from internal surfaces of raw milk road tankers, also showed that this species may produce heat‐resistant proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Serratia spp. were also detected in raw milk samples stored at 4 °C for 24 h (Lafarge and others ), in bulk tank milk (Decimo and others ) and in a milk‐processing plant (Cleto and others ), but these authors did not evaluate the capacity of heat‐resistant proteolytic enzymes production of Serratia isolates. Teh and others (), in addition to isolating S. liquefaciens from internal surfaces of raw milk road tankers, also showed that this species may produce heat‐resistant proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its extreme adaptability, versatility and ability to replicate at refrigeration temperatures, long periods of shelf life can easily lead to increased P . fluorescens concentration in food products [4, 32]. Genome-wide transcriptomic analysis is an effective method in studying adaptive responses to the environment by identifying and linking associated transcriptional perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…fluorescens is commonly part of the microflora of a wide range of food matrices, including ready-to-eat vegetables (Caldera and Franzetti, 2014), raw fish (especially sushi or sashimi), meat and dairy products (Arnaut-Rollier et al, 1999;Franzetti and Scarpellini, 2007). This is due to its extreme adaptability and versatility (Silby et al, 2011) and its ability to replicate at refrigeration temperatures (Decimo et al, 2014). Specifically, P. fluorescens can cause undesirable modifications in food products as a result of enzymatic reactions or pigmented molecule production (Andreani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%